Analysis of the Obstacles Faced by the Non-S1 PGSD PPG Participants in Mastering the Pedagogical Competence of the Merdeka Curriculum in Elementary Schools - Rahmayuni Jusar, Ira; Nora, Yulfia; Widialistuti, Refny (The Future of Education Journal, 2025)
This study aims to identify and analyze various obstacles faced by teachers participating in the Non-S1 Elementary School Teacher Education Program (PGSD) in mastering the pedagogical competencies required to meet the demands of the Merdeka Curriculum in elementary schools. Using a descriptive quantitative approach with a case study and questionnaire as data collection instruments, this research explores the challenges encountered in teaching practices. The findings reveal four main areas of difficulty for Non-S1 PGSD PPG participants. First, issues in developing lesson plans that align with the principles of the Merdeka Curriculum. Second, difficulties in managing differentiated instruction that accommodates the diverse needs of students. Third, challenges in the effective use of educational technology to support the teaching and learning process. Fourth, barriers in classroom management to create a conducive learning environment. Overall, the results of this study provide a broader perspective on the challenges teachers face in fulfilling their roles according to the evolving curriculum. It also highlights the need for more intensive training and support for Non-S1 PGSD PPG teachers to overcome these obstacles and improve the quality of education in elementary schools.